Palmar dislocation of the proximal interphalangeal joint and traumatic boutonnière deformity - Hauck, Theresa; Müller-Seubert, Wibke; Horch, Raymund E. (Unfallchirurg, 2017)
Injury to the central slip of the extensor tendon may occur with open and also with closed injuries, such as volar dislocation of the proximal interphalangeal (PIP) joint. For adequate treatment, it is necessary to identify all injured structures. Without appropriate primary management, the patient is likely to develop a subacute to chronic posttraumatic boutonnière deformity. A fixed boutonnière deformity requires recovery of joint mobility. Once joint mobility is achieved, secondary surgical reconstruction of the central slip can be performed with a tendon transfer or a tendon transplant.
EVALuna2:32836